Bi-functional ferroelectric BiFeO3 passivated BiVO4 photoanode for efficient and stable solar water oxidation. (January 2017) - Xie, Jiale; Guo, Chunxian; Yang, Pingping; Wang, Xiaodeng; Liu, Dingyu; Li, Chang Ming
Abstract: Photoelectrochemical (PEC) devices have become one of the most attractive clean energies due to its potential high efficiency and simplicity but it is very challenging to make a highly efficient and stable practical device. Up to date, BiVO4 as the most promising ternary metal-oxide photoanode can only achieve a photocurrent of no more than 1.0 mA cm −2, which is far below its theoretical value (7.5 mA cm −2 ), and is mainly caused by its high charge recombination from defects and sluggish water oxidation kinetics. Herein we fabricate a BiVO4 /ferroelectric BiFeO3 composite photoanode by a surface passivation approach to greatly enhance photocurrent by 4.4 times plus 400 mV negative shift of the onset potential than the plain BiVO4 . BiVO4 /BiFeO3 also greatly decreases charge recombination rate from 17 s −1 to 0.6 s −1 in comparison to the plain BiVO4 by 28 times. The PEC performance of BiVO4 /BiFeO3 can also be manipulated based on the direction of self-polarization in BiFeO3 . Moreover, BiVO4 /BiFeO3 shows much better stability than that of the BiVO4 as well as BiVO4 /Co-Pi. It is discovered that the PEC performance enhancement mechanism is attributed to the BiFeO3 passivation for a bifunctional film as a buffer layer to significantly reduce charge recombination while as an efficient catalyst to boost charge separation/transfer. Graphical abstract: Highlights: Ferroelectric BiFeO3 as passivation layer and catalyst is used to modify BiVO4 . BiFeO3 can suppress the charge recombination and improve the charge separation. BiVO4 /BiFeO3 shows greatly higher current and negative shift for the onset potential. BiFeO3 modified electrode also shows better stability than that of Co-Pi modified.